Behavior of dihydroxybenzenes and gallic acid on the Fenton-based decolorization of dyes. Issue 1 (2nd January 2016) - Barreto, Fernanda; Santana, Cássia Sidney; Aguiar, André
Abstract: Dihydroxybenzenes (DHBs) are used as mediators to increase the degradation of recalcitrant organic pollutants by Fenton reaction. DHBs regenerate Fe 2+ ions, resulting in the formation of OH radicals in a more intense and continuous manner than the classical Fenton reaction. The present work investigates the behavior of different DHBs and gallic acid (a trihydroxybenzene) on the decolorization of dye solutions by Fenton systems (Fe 2+ /H2 O2, Fe 3+ /H2 O2 ). For the majority of DHBs and gallic acid, pro-oxidant properties were observed on the decolorization of methylene blue, chromotrope 2R, methyl orange, and phenol red. These properties were dependent on the hydroxyl position in the aromatic ring and were highly influenced by the structure and redox potential of the target pollutant. The dye decolorization by Fenton-like reaction (Fe 3+ /H2 O2 ) in the presence of 2, 5-dihydroxybenzoic acid as mediator was more efficient than classical Fenton reaction. For example, Fe 3+ /H2 O2 /2, 5-dihydroxybenzoic acid system provided 60% of phenol red decolorization against 40% by Fe 2+ /H2 O2 after 60 min of reaction. DHBs and gallic acid increased the decolorization of dyes, requiring the highest H2 O2 consumption. However, H2 O2 consumption occurred even when the dye solutions were not extensively decolorized, suggesting that part of the generated OH radicals reacted with either DHBs, H2 O2 or other reactive species in solution.